An investigation of foundation phase teachers’ experiences of workplace bullying in Johannesburg schools - Miller, Kim Claire (My University, 2020)
Workplace bullying is a worldwide phenomenon that is known to have severe effects on an individual’s health and professional status. Workplace bullying in schools is a phenomenon that is known globally to affect teachers, and South African teachers are not excluded from this. The purpose of this study was to examine the impact that workplace bullying has on Foundation Phase teachers in Johannesburg. This study focused on the experiences of Foundation Phase teachers of workplace bullying at three schools in Johannesburg, South Africa. The primary aim of this study was to examine the lived experiences of workplace bullying of Foundation Phase teachers and to identify key factors that contribute towards workplace bullying. This study examined the impact and effects that workplace bullying has on a foundation phase teachers. This was achieved through this qualitative study that utilized a questionnaire in order to investigate the experiences and perceptions of workplace bullying by Foundation Phase teachers. It also explored the contributing factors of workplace bullying which the Foundation Phase teachers highlighted in the completed questionnaire. The theoretical framework that this research study used was based on three theories; the first theory was the organisational theory which elaborates on the structure of an organization, the second theory was the workgroup manipulation theory which focuses on the bully and how they manipulate their environment to bully other employees. Lastly, the inclusion and exclusion theory in the workplace was relevant as it highlights how certain factors and characteristics of an organisation can either enable inclusion of all employees or allow workplace bullying to occur. This study showed that teachers indicated that the main perpetrators in workplace bullying incidents varied from other teachers to head of departments, admin staff and principals. The bullying behaviours portrayed in these bullying incidents were intended to negatively impact the teacher personally and professionally. The reports in this study showed that teachers were first impacted psychologically, and this rippled into their personal and professional well-being as Foundation Phase teachers. In addition, the participants shared their experiences of how workplace bullying affected their teaching practices and suggested a few strategies to deal with workplace bullying effectively in the school environment.
Research report submitted to the Wits School of Education, University of the Witwatersrand as partial completion of the requirements set for the degree Masters in Education, 2020